Un nuevo dato biográfico sobre Cosme de Aldana - Medina Bermúdez, Alejandro (Cuadernos de Filología Italiana, 2007)
The present investigation brings to light a new piece of biographical data about Cosme de Aldana. It is shown that the poet studied law in the University of Pisa, something he himself states in his Asneyda, but which now can be proven beyond any doubt. At the same time it is here suggested that a) the Asneyda deserves being recovered from oblivion, and b) that in this as in other works Cosme provides clues (some of which are examined in the present article) that could be of great value when attempting to reconstruct his biography, a task that would contribute to a better knowledge of the 16th century in general, and of the Spanish-Italian aristocracy of that period in particular.